(untitled) (Scientific journal of the Fergana State University, 2025)
In the article, in the study of the physical chemical biological properties of soil, in the creation of a scientific basis for the selection and grouping of plant species according to the salinity of the soil-soil in the dry bottom of the Aral Sea, the radiological safety of the soil distributed in the dry bottom of the Aral Sea indicators have been studied.